MOTIVATION OF PUBLIC SERVICE IN NATIONAL LAND AGENCY IN THE CITY OF MAKASSAR - Andi Farisnah Anwar; Sangkala Sangkala; Hamsinah Hamsinah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Palu, 2018)
Efforts to improve the quality of public services in the Land Board of Makassar City have been so often done in the service of the issuance of certificates of land rights, efforts to improve the quality of public services seems to have not undergone significant changes and improvements, both improvements ineffectiveness and administrative inefficiency. This study aims to analyze the organizational values underlying employee motivation in providing the Issuance Service of Land Rights Certificate in Makassar City. The research method used is qualitative approach with case study research type. Data were analyzed by data reduction, data presentation, and conclusion. The results of this study indicate that the Motivation of Public Service in the Service of Issuance of Land Rights Certificate in applying the organization's values to the employees, that is Less Maximum because of the complaints of the society either from government institutions such as Makassar City Council, Makassar District Court and the existence of service less maximal due to land certificate issue. This shows the lack of commitment of employees in providing excellent service in accordance with the vision and mission of the organization and regulation No. 1 of 2010 pertaining to land services that have not been fully implemented as well as the rules that have been set.Â